2009
DOI: 10.5688/aj730470
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Electrocardiogram Basics Using Dance and Movement

Abstract: Objective. To implement and assess an innovative approach to teaching electrocardiogram (ECG) rhythms using dance and movement. Design. Recognition of ECG rhythms was taught to a group of third-year pharmacy students using dance and movement via collaboration with a dance faculty member. A control group was taught using traditional pharmacy lecture and PowerPoint slides. Assessment. A pretest and posttest were administered to both groups. There was a trend in test score improvement in the dance and movement gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In one such example, dance has been used to convey the basics of echocardiogram, a novel concept but difficult to adapt to all situations. 13 Lectures, however have stood the test of time and may have been unfairly criticized. A trial that compared live lectures with video podcast of the lecture found no improvement of the newer technology over the traditional lecture.…”
Section: Discussionmentioning
confidence: 95%
“…In one such example, dance has been used to convey the basics of echocardiogram, a novel concept but difficult to adapt to all situations. 13 Lectures, however have stood the test of time and may have been unfairly criticized. A trial that compared live lectures with video podcast of the lecture found no improvement of the newer technology over the traditional lecture.…”
Section: Discussionmentioning
confidence: 95%
“…However, the optimal way to learn and train ECG interpretation needs to be studied [ 4 ]. Pedagogical strategies for teaching ECG and what learning media to use vary from dance [ 5 ] on one extreme, to computer assisted learning (CAL)[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health care educators have used entertaining approaches including film analysis and creative, team-based collaborative approaches to educate students. 2,3,6,7,[9][10][11] Films generating commentary and education on health issues have been observed to be a more effective way of engaging students than standard discussions warning against adverse health effects. 6 The use of video assignments in a medical school curriculum is documented.…”
Section: Introductionmentioning
confidence: 99%
“…10 A dance activity involving collaboration between pharmacy and dance school faculty members has been used in a pharmacy curriculum to teach electrocardiogram basics, but a report of teaching a mechanism of action for a drug using dance has not been previously published. 11 In this paper, we present activities tailored to Millennial preferences to increase their engagement in learning, applying, and teaching subject material beyond reading assignments and lecture. Creativity and teamwork resulted in educational events enjoyed by the entire class.…”
Section: Introductionmentioning
confidence: 99%